Corporate Disclosure in Relation to Combating Corporate Bribery: A Case Study of Two Chinese Telecommunications Companies. Issue 3 (September 2015) - Islam, Muhammad Azizul; Haque, Shamima; Dissanayake, Thusitha; Leung, Philomena; Handley, Karen
<x xml:space="preserve">Abstract</x> This paper investigates the association between global community concerns about bribery activities and anti‐bribery disclosure practices by two Chinese telecommunication companies operating internationally, namely China Mobile and ZTE. Based on content analysis of annual reports and global news media articles over a period of 16 years from 1995–2010, the findings suggest that the changes in the level of disclosures by the two major Chinese telecommunications companies were closely associated with the level of international concerns over bribery practices within the Chinese telecommunications industry. This finding indicates that the companies adopt anti‐bribery disclosure practices in order to minimise the gap of trust (social capital) between companies themselves and global stakeholders. In this paper we argue that, for domestic companies in China, culturally constructed social capital, such as guanxi, creates a level of trust between managers and their stakeholders, which obviates the need for managers to disclose anti‐bribery performance information. However, for companies operating internationally, as social capital is inadequate to bridge the gap of trust between managers and global stakeholders, managers use disclosures of anti‐bribery performance information as a way to minimise such a gap.